Spatial fields of Antarctic sea-ice concentration anomalies for summer - Autumn and their relationship to Southern Hemisphere atmospheric circulation during the period 1979-2009 - Barreira, Sandra (2011)
Summer-autumn monthly sea-ice concentration anomaly (SICA) fields in Antarctica obtained from satellite data for the period 1979-2009 were analysed with Varimax-rotated T-mode principal component analysis (PCA). The first three PCA scores described the SICA spatial behaviour and explained 38.07% of the total variance. The related atmospheric circulation characteristics were analysed using 850 hPa height and surface air-temperature anomalies for the months clustered by the corresponding SICA composites, which were based on PCA loadings above a ±0.3 threshold. The principal characteristics of SICA can be seen between the Ross and Weddell Seas, areas that remained ice-covered during the analysis period. Elsewhere around Antarctica, small distinct characteristics occur mostly in embayments. The leading summer-autumn SICA pattern shows a structure with two centres of equal sign located one over the Weddell and the other over the Ross Sea-southwest Pacific Ocean sector and a centre of opposite sign over the Bellingshausen and Amundsen Seas. The second SICA pattern is represented by a dipóle over the Weddell Sea as a result of an increase (decrease) in sea-ice concentration in the northern sector (positive phase) and a decrease (increase) in the southern region, together with a positive (negative) centre over the Ross and Amundsen Seas. The latter pattern is characterized by equal-sign anomalies on both sides of the Antarctic Peninsula and opposite-sign centres all around Antarctica with the highest intensity over the Ross Sea.